Oral manifestations of multiple myeloma – A systematic review - Padmajaa Krishnan; Madhu Narayan; Bose Divya; T Dinesh Kumar; A Ramesh Kumar; Rajkumar Krishnan (Oral Oncology Reports)
Multiple myeloma (MM) is a multifocal neoplasm, which belongs to a group of diseases termed as plasma cell dyscrasisas caused due to malignant transformation of plasma cells. Incidence of multiple myeloma is 0.7/1,00,000 people in India and is common between the 5th and 8th decades of life with more of a male predilection. The mortality rate of MM accounts for 1 % of all cancer death globally. Pertaining to oral cavity 35 % of patients with symptomatic MM present with lytic bone lesions of jaws. In this systematic review we aim to study the various presentations of MM involving different sites of the oral cavity and variations in their clinical appearance providing a broader picture of the disease and enables us to prepare an early diagnostic workup.